Hand dexterity assessment in Parkinson's disease: construct validity of the 9-Hole peg test for the more affected hand. Issue 26 (18th December 2021) - Proud, Elizabeth; Morris, Meg E.; Bilney, Belinda; Miller, Kimberly J.; Nijkrake, Maarten J.; Munneke, Marten; McGinley, Jennifer L.
Abstract: Purpose: There is limited understanding of the characteristics and evaluation of more affected hand dexterity loss in Parkinson's disease. We described 9-Hole Peg Test performance for the more affected hand and examined the construct validity of these pegboard scores in mild to severe Parkinson's disease. Methods: This observational study analysed baseline data from a cluster-randomised controlled trial. Participants ( n = 582) completed the pegboard with their more affected hand, the Patient-Specific Index-Parkinson's Disease and Self-assessment Parkinson's Disease Disability Scale. Mean pegboard performance was summarised at each disease stage. To investigate known groups validity, we explored differences in pegboard scores between participants identifying upper limb problems in their 'top three' functional limitations, and those prioritising other limitations. Convergent validity investigated correlations between pegboard performance and self-reported hand function. Results: Pegboard performance was reduced compared with normative values, and problems with hand activities were reported at each disease stage. Significant differences in pegboard performance between the two functional limitation priority groups ( p < 0.05), and moderate correlations between pegboard dexterity and hand function (Self-assessment Parkinson's Disease Disability Scale) provided evidence for construct validity. Conclusions: People with mild to severely disabling Parkinson's disease have reduced dexterity and problems with hand function. Evidence supported the construct validity of 9-Hole Peg Test more affected hand performance. IMPLICATIONS FOR REHABILITATION: People with mild to severely disabling PD experience dexterity loss and problems with hand function. It is important for clinicians to assess dexterity and hand function in people with this movement disorder. Evidence supports the construct validity of 9-Hole Peg Test for measuring more affected hand performance in Parkinson's disease.